Impact of buckwheat flour granulation and supplementation level on the quality of composite wheat/buckwheat ginger-nut-type biscuits - Bojana Filipčev; Olivera Šimurina; Marija Bodroža-Solarov (Chiriotti Editori, 2015)
Effects of gradual wheat flour substitution with buckwheat flour in ginger-nut biscuit formulation were investigated regarding dough characteristics, physical and textural characteristics of final product assessed after baking and 30 days of storage. Buckwheat flour was added at 30, 40, 50% levels and two granulations (fine and coarse). Addition of buckwheat flour significantly increased dough hardness and decreased adhesiveness. Spread significantly increased in biscuits with 40% and 50% of coarse buckwheat flour. Biscuits containing coarse flour were harder and more fracturable than the control, whereas those with fine flour tended to be softer and less fracturable. Textural properties were significantly correlated to protein stability to heat and retrogradation tendency of starch in biscuit dough as well as moisture content.